The Challenges for Going Global in the Translation of Chinese Culture and Arts - Tao, Wei; Wang, Lidi (Pacific International Journal, 2024)
As a communicator of cultures, the translation in institutions of culture and arts has come to the fore, which has not yet been the focus of in-depth studies in China. The previous studies emphasized the overt errors in translation quality assessment on linguistic level. This paper aims at answering the questions of what are the challenges in translating Chinese culture and art in the context of institutions. For this purpose, we conducted a survey by means of semi-structured interviews from 21 museums and galleries in China, focusing on translation community, the purpose of translation, the strategies and methods of translation, and the reception of translation. The findings are that the problems in the translation of culture and arts in China have been as follows: the inadequate capacities of translation teams, and the dilemma in the purposes of translation. The findings could clarify the logical relations between the two problems, promoting the translation and dissemination work of the cultural and art institutions.